A heat dissipation conductive shielding buffer foam and its application
By attaching the conductive film layer to the buffer foam layer and adding fibrous thermal filler, the existing electromagnetic wave shielding materials have been solved, and a higher compression ratio, better thermal conductivity and shielding performance are achieved, which is suitable for the lightweight and thinning needs of electronic equipment.
Patent Information
- Application Number
- CN202210397107.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-15
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-04-15
AI Technical Summary
The existing electromagnetic wave shielding materials are costly and do not meet the lightweight requirements of electronic equipment. At the same time, their heat dissipation effect is poor, which affects the durability of electronic equipment and the processing and miniaturization of 5G electronic devices.
A heat-dissipating conductive shielding buffer foam including a buffer foam layer and a conductive film layer is adopted. The conductive film layer is adhered to the surface of the buffer foam layer by layer by layer, and fibrous thermal filler is added in combination to improve the thermal conductivity effect.
It achieves higher compression ratio and better concave and convex compliance, adapts to irregular gaps inside electronic equipment, reduces contact thermal resistance, improves thermal conductivity and shielding performance, and is suitable as a gap-filling heat dissipation shielding material between electronic components of electronic products.
Smart Images

Figure BDA0003599469990000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of foam materials, and in particular relates to a heat dissipation, conductive, shielding and buffering foam and its application. Background Art
[0002] With the rapid development of the fifth generation of mobile communication technology (5G or 5G technology for short), the introduction of high frequencies, the upgrading of hardware components, and the exponential growth of the number of networked devices and antennas, electromagnetic interference between devices and within the devices themselves is ubiquitous, and the harm of electromagnetic interference and electromagnetic radiation to electronic equipment is becoming increasingly serious, and the demand for electromagnetic shielding is becoming more and more urgent. At the same time, as the functions of electronic devices become more and more numerous and more powerful, the corresponding internal chips or electronic modules are also increasing, which will generate more heat while bringing electromagnetic wave interference.
[0003] At present, shielding covers can be used to shield the main electromagnetic wave generating components such as chips and CPUs. However, the cost of using shielding covers between larger modules such as motherboards, casings, and under-screens is high, and it does not meet the current requirements for thin and light electronic devices. At the same time, there are many irregular gaps between its components. The existence of gaps makes it difficult for the electronic module to dissipate heat, which will also reduce the buffering resistance of the electronic equipment and reduce the service life of the electronic equipment.
[0004] At present, the main way to solve the above problems is to use a composite structure foam formed by wrapping a sponge with conductive cloth to fill the gaps. However, this structure not only has the disadvantages of high hardness, large material loss and large volume, but also has poor heat dissipation effect. Generally, a composite thermal conductive sheet needs to be used at the same time, which is costly. When used inside electronic equipment, its compliance with uneven surfaces is poor, which reduces the life of electronic devices and is not conducive to the back-end 5G electronic device processing and product miniaturization. Summary of the invention
[0005] In response to one or more of the above defects or improvement needs of the prior art, the present invention provides a heat dissipating conductive shielding buffer foam and its application, which is soft and has a higher compression ratio, can better adapt to the concave and convex gap scenarios inside electronic equipment, fill interface gaps, reduce contact thermal resistance, and combine with the addition of thermally conductive fillers inside to improve the thermal conductivity effect; at the same time, the conductive film layer has good surface conductivity, so that the material can be used as an electromagnetic wave shielding material.
[0006] To achieve the above object, according to one aspect of the present invention, there is provided a heat dissipation conductive shielding buffer foam, comprising a buffer foam layer and a conductive film layer arranged on one side or both sides of the buffer foam layer, and the conductive film layer is attached to the surface of the buffer foam layer by sputtering layer by layer;
[0007] The thickness of the heat dissipation conductive shielding buffer foam is in the range of 0.06mm to 1mm, and the density is in the range of 0.03g / cm 3 ~0.8g / cm 3 The maximum compression ratio is ≥60%, the maximum pore size in each direction does not exceed 80μm, and the foam opening rate is ≤30%;
[0008] The buffer foam layer contains fibrous heat-conducting filler, and its thermal conductivity is within the range of 1w / m·k to 10w / m·k.
[0009] As a further improvement of the present invention, the thickness of the conductive film layer is within 0.03 μm to 1 μm, and the square resistance is ≤ 1Ω / □;
[0010] As a further improvement of the present invention, the aspect ratio of the fibrous thermal conductive filler is greater than 60.
[0011] As a further improvement of the present invention, the fibrous thermal conductive filler is carbon nanotubes and / or carbon nanofibers.
[0012] As a further improvement of the present invention, the added amount of the fibrous thermal conductive filler is 5% to 30%.
[0013] As a further improvement of the present invention, the conductive film layer is one or more of silver, copper, gold, aluminum, zinc or alloys thereof.
[0014] As a further improvement of the present invention, the buffer foam layer is a polymer foam with a pore structure.
[0015] As a further improvement of the present invention, the foam further comprises rubber and / or thermoplastic elastomer.
[0016] According to another aspect of the present invention, there is provided an application of the heat dissipating conductive shielding buffer foam as a heat dissipating shielding material for filling gaps between electronic components of electronic products.
[0017] In general, the above technical solution conceived by the present invention has the following beneficial effects compared with the prior art:
[0018] The heat dissipating conductive shielding buffer foam of the present invention is soft and has a higher compression ratio, and can better adapt to the concave and convex gap scenarios inside electronic equipment, fill interface gaps, reduce contact thermal resistance, and combine with the addition of thermally conductive fillers to improve the thermal conductivity effect; at the same time, the conductive film layer has good surface conductivity, so that the material can be used as an electromagnetic wave shielding material.
[0019] The heat dissipating conductive shielding buffering foam of the present invention has a multi-pore structure and has the advantages of strong gap filling ability, good buffering property, fast heat dissipation, high shielding efficiency, and being lighter and thinner. It is more suitable as a gap filling heat dissipating shielding material between electronic components of electronic products. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0021] The present invention provides a heat dissipation conductive shielding buffer foam, comprising a buffer foam layer and a conductive film layer arranged on one side or both sides of the buffer foam layer;
[0022] The thickness of the heat dissipation conductive shielding buffer foam is in the range of 0.06mm to 1mm. If the thickness is too thin, the number of cells in the thickness direction is too small, the surface is easily damaged, and the durability is poor. If the thickness of the heat dissipation conductive shielding buffer foam is too thick, it is not suitable for the current trend of lightweight and thin electronic equipment. Therefore, the thickness of the overall heat dissipation conductive shielding buffer foam is preferably in the range of 0.06mm to 1mm;
[0023] Furthermore, the density of the heat dissipation conductive shielding buffer foam is in the range of 0.03g / cm 3 ~0.8g / cm 3 Within, the maximum compression ratio is ≥60%; under this range of compression ratio, the foamed sheet is softer, can better adapt to the uneven surface in the gap between electronic equipment components, and will not produce large continuous stress on the components in the electronic equipment, and has better concave and convex compliance performance, which is also beneficial to the durability and stability of electronic equipment;
[0024] Furthermore, the maximum pore size in each direction of the heat dissipating conductive shielding buffer foam does not exceed 80μm, and the foam open porosity is ≤30%. The foam pore size and closed porosity within this range can better match the preparation process of the conductive film layer. In the layer-by-layer sputtering method used to prepare the conductive film layer, the foam is in a vacuum environment for part of the time during the sputtering process. If the pore size of the foam is too large or the closed porosity is low, the pores will expand and rupture, and many holes will appear on the surface of the foam. It is difficult for the sputtering process to fill these holes. This will cause the conductive film layer to have many broken holes on the surface of the conductive film layer after it is sputtered on the foam. The presence of broken holes will reduce the conductive uniformity of the conductive film layer, and the broken holes cannot block the penetration of electromagnetic waves, thereby affecting the shielding performance of the conductive foam.
[0025] The thickness of the conductive film layer is within 0.03μm to 1μm, and the square resistance is ≤1Ω / □. The lower the square resistance, the better the conductivity of the film surface and the better the shielding performance.
[0026] The buffer foam layer contains fibrous heat-conductive filler to improve the heat-conducting performance of the buffer foam layer. The heat conductivity coefficient of the buffer foam layer is within 1w / m·k to 10w / m·k.
[0027] Further preferably, the fibrous thermally conductive filler is carbon nanotubes and / or carbon nanofibers with an aspect ratio of >60. The fibrous structure with a higher aspect ratio makes it easier for the thermally conductive fillers to entangle and form a network. Compared with granular thermally conductive fillers, a smaller amount can be added to achieve the same thermal conductive effect. At the same time, the fibrous filler also has a certain ductility in the fiber direction, which is more conducive to the foam layer to maintain good softness while improving the thermal conductivity; and the addition amount of the fibrous thermally conductive filler is in the range of 5% to 30%. A lower addition amount prevents the thermally conductive filler from forming more continuous pathways inside the foam, and has little effect on improving the thermal conductivity of the foam. A higher addition amount increases the rigidity of the foam, making it difficult for the foam to maintain better softness and a higher compression ratio while improving the thermal conductivity.
[0028] Further preferably, the buffer foam layer is a polymer foam with a cellular structure. In order to obtain the above-mentioned polymer foam with a cellular structure, a polymer is preferably used as a foaming material of the matrix, and there is no particular limitation. For example, low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene, copolymers of ethylene and propylene, copolymers of ethylene or propylene with other α-olefins (such as butene-1, pentene-1, hexene-1, 4-methylpentene-1, etc.), copolymers of ethylene and other olefinic unsaturated monomers (olefinic unsaturated monomers such as vinyl esters, acrylic acid, acrylic acid esters, methacrylic acid, methacrylate, vinyl alcohol, etc.) and other polyolefin resins; polyurethane; acrylic resins such as polymethyl methacrylate. The high molecular weight resin for foaming can be used alone or in combination of two or more.
[0029] The polymer foam may also contain a rubber component and / or a thermoplastic elastomer component. The rubber component or thermoplastic elastomer component is not particularly limited as long as it has rubber elasticity and a high foaming ratio. For example, natural rubber or synthetic rubber such as natural rubber, polyisobutylene, polyisoprene, chloroprene rubber, butyl rubber, nitrile rubber, etc.; olefin elastomers such as ethylene-propylene copolymer, ethylene-propylene-diene copolymer, ethylene-vinyl acetate copolymer, polybutene, chlorinated polyethylene, etc.; polyester elastomers; polyamide elastomers; silicone elastomers; various thermoplastic elastomers such as polyurethane elastomers, etc. In addition, these rubber components or thermoplastic elastomer components can be used alone or in combination of two or more.
[0030] It should be noted that, within the range that does not affect the physical properties of the polymer foam, it also contains any one or more of a foaming agent, a foaming regulator, a sensitizer, a crystallization nucleating agent, a surfactant, a tension modifier, an anti-shrinkage agent, a fluidity modifier, a rheological agent, a light and heat stabilizer, a flame retardant, a plasticizer, a lubricant, a pigment, a filler, an antistatic agent, an antioxidant, and a masterbatch.
[0031] Further preferably, the conductive film layer is one or more of silver, copper, gold, aluminum, zinc or their alloys, and the sputtering process is mainly adopted to closely attach the conductive film layer to the surface of the buffer foam layer. Compared with the conventional sputtering process, the sputtering process of the present invention adopts a continuous layer-by-layer sputtering process, even if the foam layer passes through one or more target sputtering chambers, the conductive film layer is sputtered layer by layer, which can make the adhesion between the conductive film layer and the foam layer tighter, the conductive film layer has better scratch resistance, and can reduce the temperature generated by the particles adhering to the foam layer in the single target sputtering chamber, thereby preventing the polymer foam layer from being deformed by high temperature.
[0032] The thickness of the conductive film layer obtained by the sputtering process is relatively thin, and the thickness is within 0.03μm to 1μm. If the thickness is less than 0.03μm, it is difficult to obtain a low surface resistance performance, and thus a good shielding effect cannot be achieved; if the thickness is greater than 1μm, the rigidity of the metal in the conductive film layer will be obvious, and a softer foam cannot be obtained; within the preferred thickness range of the present invention, the foam has good surface conductivity, so that the conductive film layer can be used as a shielding layer for the buffer foam layer. At the same time, the metal film also has a certain ductility, so that the conductive film layer will not affect the physical properties of the buffer foam layer, such as compression performance. The foam has good compliance with bumps and grooves, and the foam can also have good surface conductivity when it is slightly deformed at the gap between bumps and grooves, making the foam shielding performance more stable.
[0033] In the embodiment of the present invention, the test method used for the foam sheet is as follows:
[0034] Foam thickness: measured based on the method described in ASTM D3574, using a base area ≥ 650mm 2 The thickness test is carried out using a special thickness gauge for soft foam. The 9-point method (the center point of the sample, the center point close to the four sides of the sample, and the points close to the four corners of the sample) is used to measure the thickness on a 10cm*10cm foam sheet sample, and the average value is calculated.
[0035] Foam density: Select a 10cm*10cm standard foam sheet sample, measure the thickness based on the method described in ASTM D3574, weigh the mass, and calculate the density.
[0036] Maximum compression ratio of foam: Determined based on the method described in ASTM D3574 standard, using an electronic tensile testing machine. Under standard laboratory conditions, the sample size is 50mm*50mm, the height is stacked to 10mm, the tester sensor is raised to about 10mm high and fixed, the displacement stress is cleared and the compression test is started, the compression speed is 5mm / min, the final loading stress is 2000N, and the compression amount when the compression deformation is maximum is recorded.
[0037] Foam open porosity: The test was completed based on the ASTM D2856 test standard to obtain the foam open porosity.
[0038] Maximum pore diameter: Under standard laboratory conditions, for each direction in which the pore diameter is to be measured, a 10mm×10mm thick specimen must be cut from the sample to be tested. Cut a test piece from the test piece at random, and the thickness of the test piece should be less than the diameter of a single pore, and try to ensure that the image is not blocked by the overlap of the pore wall. The optimal slice thickness should be determined by the average pore size of the foaming material, and the smaller pore diameter should be used as the slice thickness; use SEM to test the diameter of the pores on the test piece, and take the maximum pore diameter value as the maximum pore diameter of the sample.
[0039] Foam thermal conductivity: The test was completed based on the ASTM E1461-13 test standard to obtain the thermal conductivity of the sample.
[0040] Conductive film layer square resistance: tested using a DMR-1C four-probe square resistance meter.
[0041] Conductive film thickness: Cut the cross-section of the sample and use SEM and analysis software to calibrate the conductive film thickness.
[0042] Foam shielding effectiveness: Based on the GB / T12190:2006 test standard, the shielding effectiveness data of the electromagnetic shielding room is obtained by using the shielding effectiveness method.
[0043] In order to better understand the heat dissipation conductive shielding buffer foam and the preparation method thereof of the present invention, the following specific embodiments are provided.
[0044] Example 1
[0045] The heat dissipation conductive shielding buffer foam of this embodiment selects 50 parts by weight of low-density polyethylene (LDPE) resin as the basic resin, 30 parts by weight of ethylene-vinyl acetate copolymer (EVA) as the resin modifier, 3 parts by weight of azodicarbonamide as the foaming agent (particle size <10μm), 15 parts by weight of carbon nanotubes (aspect ratio 65) as the thermal conductive filler, and 2 parts by weight of maleic anhydride as the compatibilizer. It is melted, blended, extruded and stretched into a sheet at a temperature of 180°C; it is cross-linked by radiation with an irradiation dose of 25Mrad; it is foamed at 240°C, azodicarbonamide foams to produce gas, and the sheet is foamed into a foam with multiple pore structures, and the foam thickness is 0.3mm; a 0.05μm thick metal Ag layer is deposited on one side of the foam by a magnetron sputtering process.
[0046] The prepared heat dissipation conductive shielding buffer foam was sampled and subjected to the above test. The test results are shown in Table (1).
[0047] Example 2
[0048] The difference from Example 1 is that, in order to obtain softer and thinner foam, ethylene propylene rubber (EPR) is added as a resin modifier, 40 parts by weight of low-density polyethylene (LDPE) resin is selected as the basic resin, 25 parts by weight of ethylene-vinyl acetate copolymer (EVA) and 15 parts by weight of ethylene propylene rubber (EPR) are selected as resin modifiers, 3 parts by weight of azodicarbonamide is used as a foaming agent (particle size <10 μm), 15 parts by weight of carbon nanotubes (aspect ratio 65) are used as thermal conductive fillers, and 2 parts by weight of maleic anhydride is used as a compatibilizer. The other steps are the same as those in Example 1.
[0049] The prepared heat dissipation conductive shielding buffer foam was sampled and subjected to the above test. The test results are shown in Table (1).
[0050] Example 3
[0051] The difference from Example 2 is that in order to obtain a foam with better heat dissipation, the thermal conductive filler is replaced with 15 parts by weight of nano-carbon fibers (aspect ratio 120).
[0052] The prepared heat dissipation conductive shielding buffer foam was sampled and subjected to the above test. The test results are shown in Table (1).
[0053] Example 4
[0054] The difference from Example 3 is that the amount of thermally conductive filler added is adjusted, 44 parts by weight of low-density polyethylene (LDPE) resin is selected as the basic resin, 25 parts by weight of ethylene-vinyl acetate copolymer (EVA) and 20 parts by weight of ethylene-propylene rubber (EPR) are selected as resin modifiers, 3 parts by weight of azodicarbonamide is used as a foaming agent (particle size <10 μm), 6 parts by weight of nano-carbon fiber (aspect ratio 120) is used as a thermally conductive filler, and 2 parts by weight of maleic anhydride is used as a compatibilizer. The other steps are the same as Example 3.
[0055] The prepared heat dissipation conductive shielding buffer foam was sampled and subjected to the above test. The test results are shown in Table (1).
[0056] Example 5
[0057] The difference from Example 3 is that the amount of thermally conductive filler added is adjusted, 33 parts by weight of low-density polyethylene (LDPE) resin is selected as the basic resin, 15 parts by weight of ethylene-vinyl acetate copolymer (EVA) and 22 parts by weight of ethylene-propylene rubber (EPR) are selected as resin modifiers, 3 parts by weight of azodicarbonamide is used as a foaming agent (particle size <10 μm), 24 parts by weight of nano-carbon fiber (aspect ratio 120) is used as a thermally conductive filler, and 3 parts by weight of maleic anhydride is used as a compatibilizer. The other steps are the same as Example 3.
[0058] The prepared heat dissipation conductive shielding buffer foam was sampled and subjected to the above test. The test results are shown in Table (1).
[0059] Implementation List 6
[0060] The difference from Implementation Example 3 is that, in order to obtain foam with higher shielding effectiveness, a 0.9 μm thick metal Ag layer is deposited on one side of the foam by magnetron sputtering process.
[0061] The prepared heat dissipation conductive shielding buffer foam was sampled and subjected to the above test. The test results are shown in Table (1).
[0062] Implementation List 7
[0063] The difference from Implementation Example 3 is that, in order to obtain foam with higher shielding effectiveness, a 0.9 μm thick metal Cu layer is deposited on one side of the foam by a magnetron sputtering process.
[0064] The prepared heat dissipation conductive shielding buffer foam was sampled and subjected to the above test. The test results are shown in Table (1).
[0065] Implementation 8
[0066] The difference from Implementation Example 3 is that, in order to obtain foam with higher shielding performance, a 0.2 μm thick metal Ag layer is deposited on both sides of the foam by magnetron sputtering process.
[0067] The prepared heat dissipation conductive shielding buffer foam was sampled and subjected to the above test. The test results are shown in Table (1).
[0068] Comparative Example 1
[0069] The difference from Implementation Example 3 is that no conductive film layer is sputtered on the foam surface.
[0070] The prepared heat dissipation conductive shielding buffer foam was sampled and subjected to the above test. The test results are shown in Table (1).
[0071] Comparative Example 2
[0072] The difference from Implementation Example 3 is that the added thermal conductive filler is ordinary carbon powder (aspect ratio of 10).
[0073] The prepared heat dissipation conductive shielding buffer foam was sampled and subjected to the above test. The test results are shown in Table (1).
[0074] Comparative Example 3
[0075] The difference from Example 3 is that the amount of thermally conductive filler added is adjusted, 25 parts by weight of low-density polyethylene (LDPE) resin is selected as the basic resin, 15 parts by weight of ethylene-vinyl acetate copolymer (EVA) and 22 parts by weight of ethylene-propylene rubber (EPR) are selected as resin modifiers, 4 parts by weight of azodicarbonamide is used as a foaming agent (particle size <10 μm), 31 parts by weight of nano-carbon fiber (aspect ratio 120) is used as a thermally conductive filler, and 3 parts by weight of maleic anhydride is used as a compatibilizer. The other steps are the same as Example 3.
[0076] The prepared heat dissipation conductive shielding buffer foam was sampled and subjected to the above test. The test results are shown in Table (1).
[0077] Table (1) Examples and Comparative Examples Data Table
[0078]
[0079] The heat dissipating conductive shielding buffering foam of the present invention has a multi-pore structure and has the advantages of strong gap filling ability, good buffering property, fast heat dissipation, high shielding efficiency, and being lighter and thinner. It is more suitable as a gap filling heat dissipating shielding material between electronic components of electronic products.
[0080] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A heat dissipating conductive shielding buffer foam, characterized in that: A heat dissipation shielding material used as a gap filling material between electronic components of electronic products, comprising a buffer foam layer and a conductive film layer arranged on one side or both sides of the buffer foam layer, wherein the conductive film layer is attached to the surface of the buffer foam layer by sputtering layer by layer; The thickness of the heat dissipation conductive shielding buffer foam is in the range of 0.06mm to 1mm, and the density is in the range of 0.03g / cm 3 ~0.8g / cm 3 The maximum compression ratio is ≥60%, the maximum pore size in each direction does not exceed 80μm, and the foam opening rate is ≤30%; the thickness of the conductive film layer is within 0.03μm to 0.2μm, and the square resistance is ≤1Ω / □; The buffer foam layer contains fibrous heat-conducting filler, and the thermal conductivity of the buffer foam layer is within the range of 1w / m·k to 10w / m·k; the addition amount of the fibrous heat-conducting filler is 5% to 30%.
2. The heat dissipating conductive shielding buffer foam according to claim 1, characterized in that: The aspect ratio of the fibrous thermal conductive filler is greater than 60.
3. The heat dissipating conductive shielding buffer foam according to claim 1, characterized in that: The fibrous thermal conductive filler is carbon nanotubes and / or carbon nanofibers.
4. The heat dissipating conductive shielding buffer foam according to any one of claims 1 to 3, characterized in that: The conductive film layer is one or more of silver, copper, gold, aluminum, zinc or alloys thereof.
5. The heat dissipating conductive shielding buffer foam according to any one of claims 1 to 3, characterized in that: The buffer foam layer is a polymer foam with a pore structure.
6. The heat dissipating conductive shielding buffer foam according to any one of claims 1 to 3, characterized in that: The foam also contains rubber and / or thermoplastic elastomer.
7. Application of the heat dissipating conductive shielding buffer foam according to any one of claims 1 to 6 as a heat dissipating shielding material for filling gaps between electronic components of electronic products.
Citation Information
Patent Citations
Multifunctional foam sheet and preparation method thereof
CN107540959A
Sponge with electromagnetic shielding function and preparation method thereof
CN112592511A